Guidance and Counseling on the Dangers of Alcohol and Drug Use for the Learning Development of Adolescents in Anjatan Baru Village - Muhammad Dimas Maulid (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
This Community Service (PKM) activity was driven by concerns about the rise in juvenile delinquency in Anjatan Baru Village, Anjatan District, which includes smoking, alcohol consumption, and drug abuse. These deviant behaviors have been identified as serious obstacles to adolescent learning and health development, and have the potential to lead to legal repercussions. This program primarily aims to provide comprehensive understanding, raise awareness, and educate adolescents so they can avoid or stop these negative behaviors. The implementation method used is Guidance and Counseling through Orientation Services and Group Guidance Services, which encourage active, two-way communication. Through this intervention, it is hoped that adolescents in Anjatan Baru Village will develop a high level of awareness of the dangers of addictive substances and be able to develop their potential positively. The success of this program is a crucial step in protecting adolescents as national assets and creating a conducive environment for their development.